The government and the administration of General Studies - Muñoz García, María José (Cuadernos de Historia del Derecho, 2014)
The work involves the analysis of historical legislation on both the Government and the Administration and Services of the University (Rector, Counsellors, Cancelario, Cloister, Masters of Ceremonies, janitors, Stationary, Butlers, Scribes, Apothecaries, Masters of works, porter, sweeper , Sheriff of quietness, Directors and Royal Auditors, etc…), from Title XXXI of the second Partida of Alfonso X, to the Law 14/1970, August 4th, on General Education and Spanish Education Funding Reform.
Keywords: History of the Spanish University; Historic Legislation Government Personnel; Administration and University services.